PCR-RFLP evidences peculiarities in Spinal Muscular Atrophy among Cuban Patients - Pita Rodríguez M; Zaldívar Vaillant T; Zayas Guillot M; Alvarez González MA (Journal of Neurology, Neurological Science and Disorders - Peertechz Publications, 2017)
Spinal Muscular Atrophy (SMA) is a lethal, autosomal recessive, neurodegenerative disorder characterized by progressive muscle weakness. SMA has an incidence of 1 in 6000-10000 live-births and a carrier frequency of 1:38-50 [1]. Previous reports describe genotype and frequency differences among ethnic groups [2,3]. In around 95% SMA results from the loss of SMN1 gene [4]. SMA can be classified into five clinical grades based on age of onset and severity. Cuba has a high degree of admixture [5], and previous studies in this population report a different SMN1homozygous deletion frequency [6], and skin color distribution of SMA I [2]. In this study, a molecular characterization of one hundred sixtythree patients was performed by PCR-RFLP methods regarding gender and skin color distribution.